Drag reduction and convective heat transfer enahancement in flow through a rectangular channel - Ong, Sheng Siong. (2011)
The need to conserve energy has been an increasingly important criterion in the design of any system and numerous investigations have been conducted over the years to cut down on energy consumption by reducing drag in pipelines and district heating/ cooling systems. Drag reducing additives can be added to a flow to reduce turbulent friction. Two drag reducing additives that are commonly researched upon are high molecular weight polymers and surfactants.